Advanced Maintenance Policies for Shock and Damage Models - Zhao, Xufeng (Springer Series in Reliability Engineering,, 2018)
This book surveys the recent development of maintenance theory, advanced maintenance techniques with shock and damage models, and their applications in computer systems dealing with efficiency problems. It also equips readers to handle multiple maintenance, informs maintenance policies, and explores comparative methods for several different kinds of maintenance. Further, it discusses shock and damage modelling as an important failure mechanism for reliability systems, and extensively explores the degradation processes, failure modes, and maintenance characteristics of modern, highly complex systems, especially for some key mechanical systems designed for specific tasks.